2020
DOI: 10.5858/arpa.2020-0378-oa
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Impact of the 2018 American Society of Clinical Oncology (ASCO)/College of American Pathologists (CAP) Practice Guideline Update on Human Epidermal Growth Factor Receptor 2 Testing in Breast Cancer: A Systematic Analysis

Abstract: Context.— The global impact of the new 2018 American Society of Clinical Oncology/College of American Pathologists human epidermal growth factor receptor 2 (HER2) practice guideline update on the overall HER2 status designation, compared with the prior 2013 iteration, is unknown. Objectives.— To report the quantitative impact of the new guideline on HER2 status distribution. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Fifteen (6.4%) of our cases were reclassified when the 2018 HER2 ASCO/CAP criteria were applied. Similarly, Wei et al showed, in their systematic analysis, that 7.1% of HER2 FISH results were reclassified using the 2018 ASCO/CAP criteria 13 . Reclassification rates of other studies are shown in Table 3 14–18 .…”
Section: Discussionmentioning
confidence: 87%
“…Fifteen (6.4%) of our cases were reclassified when the 2018 HER2 ASCO/CAP criteria were applied. Similarly, Wei et al showed, in their systematic analysis, that 7.1% of HER2 FISH results were reclassified using the 2018 ASCO/CAP criteria 13 . Reclassification rates of other studies are shown in Table 3 14–18 .…”
Section: Discussionmentioning
confidence: 87%
“…For each antibody, positive and negative controls were included in each slide run. ER, PgR, and HER2 status were assessed according to the latest breast biomarker reporting guidelines published by the College of American Pathologists (CAP) in June 2021 23,24 . According to the updated recommendations from the International Ki67 Breast Cancer Working Group, a cut‐off value of ≥30% was used to define the high proliferation group 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Hormone receptors (HR) (i.e., estrogen receptor (ER), progesterone receptor (PgR)), Ki67, and HER2 status were updated to the breast biomarker reporting guidelines v1.4.1.1 published by the College of American Pathologists in November 2021 [ 29 , 30 , 31 ]. Then, lymphocyte subtyping was performed by immunohistochemistry (IHC) using antibodies against PD-L1 (clone 22C3), forkhead box P3 (FOXP3), CD4, and CD8 on an automated staining platform (i.e., Dako Omnis, Agilent, Santa Clara, CA, USA) on 4 µm-thick TMA sections, as previously described [ 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%